Institusioneel vasgeloop? Die Nederduitsch Hervormde Kerk van Afrika - Steenkamp, Petrus L. (HTS teologiese studies, 2017)
The Netherdutch Reformed Church (Nederduitsch Hervormde Kerk van Afrika) finds itself in a precarious situation. It could be described as a watershed moment in the life of this denomination. The impasse developed due to various factors such as the loss of membership, the economic situation, ecumenical isolation and various other influences, which eventually resulted in a strong institutionalised organisation. Institutionalisation necessarily resulted in a shift of focus from the essence of being Church towards institutional continuation. As a result, the organic growth of the church suffered. This article investigates the institutionalism of the Netherdutch Reformed Church from an open (living) systems perspective, thereby identifying the dysfunctionality between form and function and ending with certain perspectives in respect of a change in focus by the church to realise the true essence of being Church of Jesus Christ.